2020
DOI: 10.1002/cti2.1127
|View full text |Cite
|
Sign up to set email alerts
|

High‐dimensional analyses reveal a distinct role of T‐cell subsets in the immune microenvironment of gastric cancer

Abstract: Objectives. To facilitate disease prognosis and improve precise immunotherapy of gastric cancer (GC) patients, a comprehensive study integrating immune cellular and molecular analyses on tumor tissues and peripheral blood was performed. Methods. The association of GC patients' outcomes and the immune context of their tumors was explored using multiplex immunohistochemistry (mIHC) and transcriptome profiling. Potential immune dysfunction mechanism/s in the tumors on the systemic level was further examined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…However, Wang et al. showed that GC patients with higher levels of CD4+ T cells were associated with a good prognosis ( 50 ), which was consistent with the findings of the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, Wang et al. showed that GC patients with higher levels of CD4+ T cells were associated with a good prognosis ( 50 ), which was consistent with the findings of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Shen et al indicated that CD4 + T cells were related with more advanced stages of gastric cancer (48); Kindlund et al also found that CD4 + regulatory T cells can enhance tumor proliferation mediated by IL-10 and TGF-b (49). However, Wang et al showed that GC patients with higher levels of CD4+ T cells were associated with a good prognosis (50), which was consistent with the findings of the current study.…”
Section: +++ ++ + + + ++ + ++ ++ ++ + + ++ + + + + ++ + + + + + + + +supporting
confidence: 90%
“…International Publisher revealed that many solid tumors are associated with immune cell infiltration in the tumor immune microenvironment (TIME) which affects therapy efficacy and overall survival to no small extent [7][8][9]. A study revealed that high T-cell subsets density in gastric cancer was associated with prolonged survival [10]. What is more, it was thought that natural killer cells and dendritic cells were promising targets of immunity therapy for gastric cancer [11,12].…”
Section: Ivyspringmentioning
confidence: 99%
“…With relative high cellular throughput and high dimensions, CyTOF is an ideal and potent technique that reveals intratumor heterogeneity in a variety of tumors, including breast, [70][71][72][73] lung, [74][75][76][77] oropharyngeal, 78 brain, [79][80][81][82][83] colon, 7,11,84,85 ovarian, 86,87 kidney, 88,89 gastric cancer, 90,91 leukemia and lymphoma, 19,[92][93][94][95] and melanoma. 96,97 A summary of single-cell CyTOF studies on primary tumors of various human cancers is presented in Table 3.…”
Section: Cancermentioning
confidence: 99%